Meckel’s diverticulum: a rare cause of small bowel obstruction in an adult - Jabeen, Nusrat; Abdulla, Hussain Adnan; Alqaseer, Asma; Abushwemeh, Mohamed Ayed; Alrayes, Amal (International Surgery Journal, 2021)
Meckel’s diverticulum is the most common congenital abnormality of the gastrointestinal tract. Complications involving Meckel’s diverticulum include bleeding, bowel obstruction and inflammation. We present a rare case of small bowel obstruction caused by Meckel’s diverticulum. A 50-year-old male presented to the emergency department with abdominal pain and vomiting. Computed tomography (CT) abdomen showed dilated small bowel loops with transition zone at the mid ileum, consistent with small bowel obstruction. The patient was taken to the operating theatre for exploratory laparotomy and was found to have a Meckel’s diverticulum causing mechanical small bowel obstruction, which was resected with primary anastomosis. The patient recovered with no postoperative complications and was discharged home. Meckel’s diverticulum is difficult to diagnose preoperatively since most patients are asymptomatic and requires a high index of suspicion. In patients presenting with an acute abdomen, it may be overlooked because of nonspecific symptoms. In the case of small bowel obstruction, Meckel’s diverticulum should be kept in mind as part of the differential diagnosis.